Endourological management of forgotten double J stents: case series - Yadav, Chandra S.; Kunwar, Ashok Kumar; Shrestha, Sanjesh; Tiwari, Kabir; Upadhyay, Amit Mani; Dangal, Ganesh (Journal of Chitwan Medical College, 2019)
Putting ureteral stents are an integral part of urological practice. However, stents that fragment or are forgotten for a long time pose a management challenge and also legal dilemma. Our series consists of a review of five patients with forgotten double J stents. All these cases were managed at Kathmandu Model Hospital and all the forgotten stents were retrieved endourologically. Management of such complicated ureteral stents requires a multimodal therapeutic approach incorporating the latest ESWL and endourological techniques. Proper counseling to the patient with reference from post-operative KUB X-ray may prevent this urological tragedy.